ORGANIZATIONAL STRUCTURE AND SPECIFIC ASPECTS OF STUDENTS' TECHNOLOGY "IMPROVEMENT OF THE METHODOLOGY OF INDEPENDENT WORK ACTIVITY IN THE INFORMATIONAL EDUCATIONAL ENVIRONMENT" (Web of Teachers: Inderscience Research, 2023)
The importance of the problem in the teaching of mathematics is very great, and it is appropriate to use practical and non-standard problems in the educational process to increase students' interest in mathematics, to form the basis and competences related to science.